(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Football is one of the most popular sports in the world; however, it is also characterized by a high level of injuries. Significant physical exertion, high-speed sprints, sudden changes in movement direction, and physical contact substantially increase the risk of serious injuries. To reduce injury rates and improve players’ physical conditioning, the FIFA 11+ program was developed as a comprehensive injury prevention approach. This article analyzes the structure and effectiveness of FIFA 11+ and its impact on different groups of football players, including professionals, amateurs, juniors, and women. Special attention is given to the issue of specific football-related injuries, which frequently occur among players, such as anterior cruciate ligament (ACL) tears, hamstring strains, ankle ligament injuries, and groin muscle damage. A review of scientific studies has demonstrated that using FIFA 11+ can reduce the risk of injuries by 30-50%. The program has proven particularly effective for youth and women’s football, where the risk of severe injuries is higher. The study also examines the implementation of FIFA 11+ across different football teams, ranging from youth academies to national teams. Several unresolved aspects requiring further research have been identified, including program adaptation for different age groups, the long-term impact on the musculoskeletal system, and comparisons between FIFA 11+ and other injury prevention methods. To enhance the effectiveness of FIFA 11+ implementation, it is recommended to: perform exercises before every training session and match; provide coach education on proper execution techniques; motivate players to incorporate the program systematically; adapt exercises to the specific needs of various age and skill groups. The article highlights the importance of systematically integrating FIFA 11+ into football training programs to protect players’ health and improve their sports performance.